SIMULATION MODELING OF THE UNIVERSITY PERSONNEL MANAGEMENT SYSTEM - Kryukov, С.В. (Journal of Information Technologies in Education (ITE), 2014)
The article is devoted to the improvement of the university personnel management system in Russia. Simulation model of teacher’s career at the university is presented. The model is founded on system dynamics principles. It is necessary to change salary scale at the universities of Russia. It will be good for the reasons of conservation of correct proportion amongst assistants and professors and increasing level of teacher’s motivation.